Group phenotypic composition in cancer - Capp, Jean-Pascal; DeGregori, James; Nedelcu, Aurora M; Dujon, Antoine M; Boutry, Justine; Pujol, Pascal; Alix-Panabières, Catherine; Hamede, Rodrigo; Roche, Benjamin; Ujvari, Beata; Marusyk, Andriy; Gatenby, Robert; et al. (eLife, 2021)
Although individual cancer cells are generally considered the Darwinian units of selection in malignant populations, they frequently act as members of groups where fitness of the group cannot be reduced to the average fitness of individual group members. A growing body of studies reveals limitations of reductionist approaches to explaining biological and clinical observations. For example, induction of angiogenesis, inhibition of the immune system, and niche engineering through environmental acidification and/or remodeling of extracellular matrix cannot be achieved by single tumor cells and require collective actions of groups of cells. Success or failure of such group activities depends on the phenotypic makeup of the individual group members. Conversely, these group activities affect the fitness of individual members of the group, ultimately affecting the composition of the group. This phenomenon, where phenotypic makeup of individual group members impacts the fitness of both members and groups, has been captured in the term ‘group phenotypic composition’ (GPC). We provide examples where considerations of GPC could help in understanding the evolution and clinical progression of cancers and argue that use of the GPC framework can facilitate new insights into cancer biology and assist with the development of new therapeutic strategies.
Keywords: cancer biology; ecology; medicine; evolutionary biology